2008
DOI: 10.3102/0002831208316955
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teachers’ Assessment Practices Through Professional Development: The Case of National Board Certification

Abstract: This study examines how mathematics and science teachers’ classroom assessment practices were affected by the National Board Certification process. Using a 3-year, longitudinal, comparison group design, evidence of changes in teachers’ classroom practice were measured on six dimensions of formative assessment. The National Board candidates began the study with lower mean scores than the comparison group on all six assessment dimensions;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 19 publications
1
54
0
5
Order By: Relevance
“…McMunn et al further emphasized that ongoing, sustained professional development is more effective than one-time, ad-hoc workshops to support teachers' efforts at improving their assessment practices. Sato, Wei, and Darling-Hammond (2008) conducted a longitudinal study to track the changes of mathematics and science teachers' classroom formative practices as a result of their participation in the National Board Certification process. The National Board Certification provided teachers with professional development in using rigorous assessment and teaching standards.…”
Section: Teaching Education 257mentioning
confidence: 99%
“…McMunn et al further emphasized that ongoing, sustained professional development is more effective than one-time, ad-hoc workshops to support teachers' efforts at improving their assessment practices. Sato, Wei, and Darling-Hammond (2008) conducted a longitudinal study to track the changes of mathematics and science teachers' classroom formative practices as a result of their participation in the National Board Certification process. The National Board Certification provided teachers with professional development in using rigorous assessment and teaching standards.…”
Section: Teaching Education 257mentioning
confidence: 99%
“…Additionally, contextual constraints such as lack of preparation time, participation in other non-related teaching activities, students' absenteeism, and selection of inappropriate curriculum materials for instruction can reduce the perceived quality of a teacher (Kennedy, 2010). Therefore, the certification process in countries such as the United States, in which teachers reflect on their instructional practices and then have chances to adjust their thinking during their portfolio development process is influenced by these contextual factors (Sato, Wei, & Darling Hammond, 2008).…”
Section: Defining Teacher Qualitymentioning
confidence: 99%
“…In the framework of this program teachers are asked to analyze their teaching methods and the needs of the pupils, to present videos on their teaching approach and to suggest ways of developing their pupil's achievements and creativity. A study which examined the influence of this program found that the majority of teachers who took part in this program reported a significant improvement in their teaching techniques after participating in the program (Sato, Wei & Darling-Hammond, 2008). Beyond this specific program, the great advantage of formal professional development programs is that they can be monitored and the effects can be examined more accurately than non-formal programs (Little, 2006).…”
Section: International Education Researchmentioning
confidence: 99%